ACTIVITY BASED LEARNING WITH KAHOOT FOR DEVELOPING VIETNAMESE VOCABULARY LEARNING ABILITY OF STUDENTS AT MAHASARAKHAM UNIVERSITY - Nguyen Thu, Hoai; Jumlongnark, Worrawoot; Cao Thi Hong , Van (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The purposes of this research were: 1) to determine the efficiency of Activity based learning with Kahoot for developing Vietnamese vocabulary learning ability of students at Mahasarakham University with 80/80 criteria of effectiveness, 2) to compare the ability to learn Vietnamese vocabulary before and after learning management, 3) to study the retention of Vietnamese vocabulary after using the learning management with Kahoot. The sample of this research was 39 students who registered the subject 004 1017 Vietnamese for Communication, Mahasarakham University, semester 1/2023 which was obtained by Simple Random Sampling by using the classroom drawing method random unit. The experimental research instruments consisted of lesson plans and the Vietnamese vocabulary test. Statistics for data analysis include mean, standard deviation, and dependent samples t-test. The results of the research appeared as follows: 1) Activity based learning with Kahoot for developing Vietnamese vocabulary learning ability of students at Mahasarakham University was 80.82/79.36 which exceeded the threshold of 80/80. 2) Vietnamese vocabulary learning ability of students at Mahasarakham University after using of Activity based learning with Kahoot were significantly higher than before used at .0 5 level. 3) The students’ retention English vocabulary after 2 weeks was 30.90 out of 40, not below 70% and the result was not significantly different from posttest at .0 5 level.